UI/UX Design of Higher Education Academic Information System for Users with Low Digital Literacy - Pratiwi Bagus Nanindah; Teduh Dirgahayu (Journal of Science and Education (JSE), 2026)
Academic Information Systems (AIS) play a crucial role in supporting academic activities at universities. However, at STIE Indonesia Pontianak, academic information management is still partially conducted manually and is difficult to access; additionally, some students have low digital literacy, which causes difficulties in using complex systems. This study aims to design a simple and user-friendly AIS interface prototype using a User-Centered Design (UCD) approach within the framework of the Design Science Research Methodology (DSRM). Data collection was conducted through observation using the think-aloud method and interviews. The design outcome, a high-fidelity prototype, was then evaluated using task-based usability testing and the System Usability Scale (SUS). Test results showed that the success rate for the low digital literacy group was 99%, while for the high digital literacy group it reached 100%. SUS scores indicated that the low literacy group received a score of 69 (marginal category), while the high literacy group received a score of 81.4 (acceptable category). These results indicate that the prototype has good usability, but still requires improvement for users with low digital literacy. The resulting prototype can serve as a reference in the development of user-centered AIS.